CULPABILIDAD Y RESPONSABILIDAD PERSONAL EN LAS SANCIONES ADMINISTRATIVAS EN MATERIA DE DEFENSA DE LA COMPETENCIA EN EL DERECHO EUROPEO Y ESPAÑOL - Laguna de Paz, José Carlos (Revista de Derecho, 2019)
The imposition of administrative sanctions for breach of competition law must respect the principles of personal responsibility and culpability. In this sense, it is required that the action has been autonomously decided by the company. For the same reason, the principle of legitimate expectations can exclude liability. The direct responsibility of the companies is complemented by the responsibility of the managers. Spanish legislation affirms the principle of joint and several liability in cases of multiple authorship. Breaches of competition law by companies forming part of a group can be attributed to the parent company, unless its subsidiary acted autonomously. Responsibility is not always extinguished in case of business and organizational changes and companies succession.